Improvement in Impaired Social Cognition but Not Seizures by Everolimus in a Child with Tuberous Sclerosis-Associated Autism through Increased Serum Antioxidant Proteins and Oxidant/Antioxidant Status - Kunio Yui; George Imataka; Hitomi Sasaki; Yohei Kawasaki; Tohru Okanshi; Ryoichi Shiroki; Shigemi Yoshihara (Case Reports in Pediatrics)
We investigated the effect of the mammalian target of rapamycin (mTOR) inhibitor everolimus on tuberous sclerosis complex- (TSC-) associated autistic symptoms and focal seizures with impaired awareness in a female child with TSC. We further evaluated the relationship between improved autistic symptoms and seizures and increased the serum levels of the antioxidant proteins, ceruloplasmin (Cp) and transferrin (Tf), and oxidant-antioxidant status indicated by the oxidant marker oxidized low-density lipoprotein (ox-LDL) and the antioxidant marker total antioxidant power (TAP). Everolimus treatment improved impaired social cognition and autistic behaviors; however, seizure and epileptic activity persisted. Serum Cp and Tf levels gradually increased in response to improved autistic symptoms. Serum TAP levels gradually decreased from baseline to the lowest value at 16 weeks and then increased at 24 weeks, showing a trend toward decreased total score of the Aberrant Behavior Checklist. This study revealed that everolimus treatment improved impaired social cognition with increased serum levels of the copper mediator (Cp) and iron mediator (Tf) via homeostatic control of mTOR activity accompanied by overlap of the oxidant-antioxidant system. Everolimus had no effect on TSC-related epileptiform discharges, and thus, the autistic symptoms and epileptic activity may be two independent end results of a common central nervous system disorder including mTOR hyperactivity. This trial is registered with JMAS-IIA00258.